2017
DOI: 10.4172/2155-9937.1000139
|View full text |Cite
|
Sign up to set email alerts
|

The Role of PET/CT in the Diagnosis of Kikuchi-Fujimoto Disease: A Case Series and Review of the Literature

Abstract: Introduction: Kikuchi-Fujimoto disease (KFD), also known as Kikuchi's disease or histiocytic necrotizing lymphadenitis, is a self-limiting case of non-cancerous lymphadenopathy. Although previous reports have demonstrated its physical findings and traditional imaging characteristics, few studies mentioned the application of 18 fluorodeoxyglucose positron emission tomography-computed tomography ( 18 F-FDG PET/CT) imaging in the diagnosis and follow-up of this disease. Here, we present three cases of KFD, descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Reports show KFD's predilection for cervical lymphadenopathy, small-or medium-sized similar to our case. Nodal involvement is usually discrete and involves levels II, III, and IV with CT findings of low attenuation nodes [6]. In our study, we found bilateral involvement of discrete supradiaphragmatic (cervical, axillary, and deep pectoral) along with fewer infra diaphragmatic (periportal, portocaval and inguinal) nodal involvement.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Reports show KFD's predilection for cervical lymphadenopathy, small-or medium-sized similar to our case. Nodal involvement is usually discrete and involves levels II, III, and IV with CT findings of low attenuation nodes [6]. In our study, we found bilateral involvement of discrete supradiaphragmatic (cervical, axillary, and deep pectoral) along with fewer infra diaphragmatic (periportal, portocaval and inguinal) nodal involvement.…”
Section: Discussionsupporting
confidence: 58%
“…Thus, "string of pearls sign" is a non-specific PET finding and can be present in nodal disease of diverse etiologies Anatomic and functional imaging procedures like CT and PET are not diagnostic for KFD. The affected lymph nodes in KFD appear enlarged, lose their normal shape, and acquire an abnormal round shape with associated FDG avidity indicating infection, inflammation, or a neoplastic underlying pathology [6]. The nodes may show unilateral or bilateral involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation